Eсological epidemiological features of desease of the malignant new growths of the population of Makhachkala of Dagestan Republic - A. V. Ryabova; A. G. Gasangadjiyeva; Z. I. Gadjiyeva (Юг России: экология, развитие, 2015)
There was organized the analysis of epidemiology of malignant new growths in Makhachkala (Daghestan Republic). In purpose of physician-ecological estimation of the studied region retrospective analysis of cancer decease was accomplished, there was also determined standardized factors and ratios of correlations at time. Components of environment(atmospheric air, soil and water) were chemically tested.